Efektifitas Mobilisasi Saraf Dan Nerve Gliding Dalam Penurunan Nyeri Pada Carpal Tunnel Syndrome - Pangestu, Nugrahati Dwi, Agus Widodo, S.Fis., M.Fis (2016)
BACKGROUND OF THE STUDY: In patients with carpal tunnel syndrome is known that there is a suppresion on the median nerve. This leads to pain and disturbance functional activities. OBJECTIVES OF THE STUDY: To determine the effectiveness of the mobilization of nerves and nerve gliding in decreasing pain in the carpal tunnel syndrome. RESEARCH METHODOLOGY: This research used Quasi Experiment method. Quasi-experiment is a study by conducting experiments that aims to identify the symptoms or effect, as a result of their particular treatment or experiments. In this study the author used pre-test and post-test methods. RESULTS OF THE STUDY: The data obtained were not normally distributed, statistical tests using the Wilcoxon test to determine the effect of pain pretest and post test in the group treated with the mobilization of nerves and nerve gliding, with the result of p 0.008 and 0.011 or p <0.05 so that Ha accepted which means there is effect of nerves mobilization therapy and nerve gliding towards carpal tunnel syndrome pain reduction and Mann Whitney test knowing the different effect of nerve mobilization treatment with nerve gliding, with the result of p: 0.009 or p <0.05 so that Ha is accepted, which means there is different influences on nerve mobilization therapy with nerve gliding where nerve mobilization is more effective against pain reduction in carpal tunnel syndrome. CONCLUSION: It is concluded that there are differences in the effect of nerve mobilization with nerve gliding towards pain reduction of carpal tunnel syndrome.